Concentración de compuestos orgánicos volátiles y material particulado en ambientes urbanos e industriales de dos regiones bonaerenses : Estudio comparativo entre La Plata y Bahía Blanca - Colman Lerner, Jorge Esteban (2012)
We present the results of a study of ambient air quality in two regions comparable Buenos Aires, developed jointly by the Center for Environmental Research (Faculty of Exact Sciences, UNLP), the Sanitary Engineering Laboratory (Faculty of Engineering, UNLP) and Department of Chemistry, National University of the South, between 2009 and 2011. In the same measure levels of environmental pollutants (volatile organic compounds, VOCs) and particulate matter suspended in air (MP) in air walls. The regions studied include the cities of Bahia Blanca and La Plata, also considering its surroundings. Both are characterized by a petrochemical complex and a village with outstanding traffic. Current concern for these contaminants is its action on human health, both as an irritant of mucous membranes, conjunctiva and nervous system, for its effects on lung function, triggering chronic obstructive diseases. 20 VOCs were sampled by passive monitoreadores (3M 3500) and particulate matter (PM10) using a low flow sampler MiniVol TAS, in private homes and schools in both regions, in three areas: urban, industrial and residential (reference area) VOC levels were determined by GC/FID, comprising alkanes (hexane, decane, dodecane, cyclohexane and methylcyclohexane), aromatic compounds (benzene, toluene, ethylbenzene and xylenes) and chlorinated compounds (trichlorethylene and tetrachlorethylene). PM10 content was determined gravimetrically. The collected data show higher levels of PM10 in La Plata on Bahia Blanca in all study areas. However, the levels of total VOCs found in La Plata are lower than those determined in Bahia Blanca in industrial and urban areas, reversing the relationship in the residential area.